Familial, Societal and Situational Factors Influencing Career Choice among Adult Learners in Ghana: Familial, Societal and Situational Factors Influencing Career Choice - Fenu , Ignatius Kofi; Amponsah, Samuel; Nkum , Wilson Kwesi (Journal of Interdisciplinary Studies in Education, 2021)
This study delved into uncharted grounds in the Ghanaian context as it sought to determine the familial, societal and situational factors influencing career choice among adult learners. A sample of 350 respondents was selected through multi-stage sampling and engaged in this quantitative cross-sectional survey. Analysis of the data showed that there were statistically significant relationships between specific familial, societal and situational factors and the career choices of the respondents of this study. As a result, putting in place school counsellors to orient parents and guardians on career opportunities, teachers living exemplary lives and orienting trainee teachers to develop a positive attitude towards teaching were seen as imperatives in avoiding high turnover rate among professional teachers.